Attenuating Colorectal Cancer Using Nine Cultivars of Australian Lupin Seeds: Apoptosis Induction Triggered by Mitochondrial Reactive Oxygen Species Generation and Caspases-3/7 Activation - Kishor Mazumder; Asma Aktar; Sujatha Ramasamy; Biswajit Biswas; Philip G. Kerr; Christopher Blanchard (Cells, 2023)
As Australian lupin cultivars are rich sources of polyphenols, dietary fibers, high-quality proteins, and abundant bioactive compounds with significant antioxidant, antidiabetic, and anticancer activities, this research work is aimed at investigating the colon cancer alleviation activity of nine cultivars of lupin seeds on HCT116 and HT29 colon carcinoma cell lines through anti-proliferation assay, measurement of apoptosis, and identification of the mechanism of apoptosis. Nine cultivars were pre-screened for anti-proliferation of HCT116 and HT29 cells along with consideration of the impact of heat processing on cancer cell viability. Mandelup and Jurien showed significant inhibition of HCT116 cells, whereas the highest inhibition of HT29 cell proliferation was attained by Jurien and Mandelup. Processing decreased the anti-proliferation activity drastically. Lupin cultivars Mandelup, Barlock, and Jurien (dose: 300 μg/mL) induced early and late apoptosis of colon cancer cells in Annexin V-FITC assay. The mechanism of apoptosis was explored, which involves boosting of caspases-3/7 activation and intracellular reactive oxygen species (ROS) generation in HCT116 cells (Mandelup and Barlock) and HT29 cells (Jurien and Mandelup). Thus, the findings showed that lupin cultivars arrest cell cycles by inducing apoptosis of colorectal carcinoma cells triggered by elevated ROS generation and caspases-3/7 activation.